Postoperative Complications of Scleral Buckling. (2nd January 2018) - Papakostas, Thanos D.; Vavvas, Demetrios
ABSTRACT: Scleral buckling has an important role in the repair of certain categories of rhegmatogenous retinal detachments. These include detachments in young phakic patients, detachments associated with dialysis, and also in conjuction with vitrectomy in patients who have sustained trauma or have developed proliferative vitreoretinopathy. However, it can be associated with significant postoperative complications. The most important ones are refractive change, intrusion or extrusion, infection, globe ischemia, and choroidal detachments, amongst others. Careful planning, appropriate patient selection, and good intraoperative technique can reduce the rate of these complications.